Complementary Tendencies in the Use of Regulatory Elements (Transcription Factors, Sigma Factors, and Riboswitches) in Bacteria and Archaea - Chávez, Joselyn (J Bacteriol, 2020)
In prokaryotes, the key players in transcription initiation are sigma factors and transcription factors that bind to DNA to modulate the process, while premature transcription termination at the 5′ end of the genes is regulated by attenuation and, in particular, by attenuation associated with riboswitches. In this study, we describe the distribution of these regulators across phylogenetic groups of bacteria and archaea and find that their abundance not only depends on the genome size, as previously described, but also varies according to the phylogeny of the organism. Furthermore, we observed a tendency for organisms to compensate for the low frequencies of a particular type of regulatory element (i.e., transcription factors) with a high frequency of other types of regulatory elements (i.e., sigma factors). This study provides a comprehensive description of the more abundant COG, KEGG, and Rfam families of transcriptional regulators present in prokaryotic genomes. IMPORTANCE In this study, we analyzed the relationship between the relative frequencies of the primary regulatory elements in bacteria and archaea, namely, transcription factors, sigma factors, and riboswitches. In bacteria, we reveal a compensatory behavior for transcription factors and sigma factors, meaning that in phylogenetic groups in which the relative number of transcription factors was low, we found a tendency for the number of sigma factors to be high and vice versa. For most of the phylogenetic groups analyzed here, except for Firmicutes and Tenericutes, a clear relationship with other mechanisms was not detected for transcriptional riboswitches, suggesting that their low frequency in most genomes does not constitute a significant impact on the global variety of transcriptional regulatory elements in prokaryotic organisms.